2013
DOI: 10.1016/j.jconrel.2012.11.013
|View full text |Cite
|
Sign up to set email alerts
|

High levels of ephrinB2 over-expression increases the osteogenic differentiation of human mesenchymal stem cells and promotes enhanced cell mediated mineralisation in a polyethyleneimine-ephrinB2 gene-activated matrix

Abstract: Gene therapy can be combined with tissue engineering constructs to produce gene-activated matrices (GAMs) with enhanced capacity for repair. Polyethyleneimine (PEI), a non-viral vector, has previously been optimised for high efficiency gene transfer in rat mesenchymal stem cells (rMSCs). The use of PEI to transfect human MSCs (hMSCs) with ephrinB2 is assessed here. Recently a role for the ephrinB2 ligand and EphB4 receptor duo has been proposed in bone remodelling. Herein, over-expression of the ephrinB2 ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 53 publications
1
46
0
Order By: Relevance
“…Recently, there has been a surge in research to combine gene therapy with scaffold-based templates to produce gene-activated matrices (GAMs), enhancing the capacity for repair. The scaffold acts as a depot for the gene while simultaneously providing both structural support and a matrix for new tissue deposition (Storrie and Mooney, 2006;O'Rorke et al, 2010;Curtin et al, 2012;Tierney et al, 2012a).…”
Section: In Situ Tissue Regeneration By Native Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been a surge in research to combine gene therapy with scaffold-based templates to produce gene-activated matrices (GAMs), enhancing the capacity for repair. The scaffold acts as a depot for the gene while simultaneously providing both structural support and a matrix for new tissue deposition (Storrie and Mooney, 2006;O'Rorke et al, 2010;Curtin et al, 2012;Tierney et al, 2012a).…”
Section: In Situ Tissue Regeneration By Native Cellsmentioning
confidence: 99%
“…Changing the composition of biomaterials used in scaffold fabrication can lead to a difference in ligand availability and subsequent integrin binding. Tierney et al (2009) demonstrated that altering the concentration of collagen and glycosaminoglycans (GAGs) in a collagen-GAG scaffold had a significant influence on osteoblast activity, indicating an effect of differing ligand availability (Tierney et al, 2009a;Tierney et al, 2012a). Furthermore, altering the composition of biodegradable scaffolds developed for cartilage repair has led to improved in vivo stability and increased matrix deposition (Moutos et al, 2007).…”
Section: Murphy Et Al Cell-scaffold Interactionsmentioning
confidence: 99%
“…62 The newly discovered role of ephrinB2 and EphB4 interactions in bone prompted the investigation of the overexpression of the ephrinB2 ligand in a GAM in a follow on paper which was also published in the Journal of Controlled Release in 2013. 56 First, in this study, it was shown that ephrinB2 overexpression increases osteogenesis in monolayer human MSCs which was dependent upon an interaction with the EphB4 receptor presented on the surface of adjacent cells. This led to the establishment of a novel PEI-ephrinB2 GAM specifically tailored for bone repair which Figure 2.…”
mentioning
confidence: 75%
“…This goal has since been achieved in the interim by incorporating plasmid DNA encoding the ephrinB2 gene. 56 Ephrin ligands and their cognate receptors are involved in governing many cellular processes from cell morphology to vasculogenesis and cell migration. 57,58 Of most relevance to orthopedic applications, it has been shown that some ephrin ligands and receptors, namely ephrinB2 and EphB4, are involved in bone remodelling.…”
mentioning
confidence: 99%
“…[96,124] Studies on scaffold-based gene delivery in the lab originally began with the delivery of pDNA including BMP2 [95] and combinations of BMP2 and VEGF [155] utilizing the nHA particles [94] and coll-nHA scaffolds [94,156] developed in-house specifically for bone repair. Having demonstrated the dramatically enhanced therapeutic potential of such systems not only for bone but also cartilage and nerve repair, we also progressed to investigating the utility of alternative gene delivery vectors including PEI, [85,155,157] chitosan, [40,158] Lipofectamine 2000, [75] and cyclodextrin, [75,159] different genetic cargo such as pDNA, [85,95,155,157] miRNA, [96,124] and siRNA, [75,159] and various scaffold types including collagen alone, [85,95] collagennHA, [75,95,96,124,155,159] collagen-HA [85] and collagen hyaluronic acid (coll-HyA) [85] to tailor our systems depending on the final application required. [158] Delivery of the miR-mimics and miR-inhibitors from porous collagen-nHA scaffolds yielded very promising results demonstrating silencing functionality of ≈20% and 88.4%, respectively.…”
Section: Osteogenesis and Bone Repairmentioning
confidence: 99%